A maintenance system model for optimal reconfigurable vibrating screen management - O. A. Makinde; K. Mpofu; B. I. Ramatsetse; M. K. Adeyeri; S. P. Ayodeji (Journal of Industrial Engineering International, 2018)
The reconfigurable vibrating screen (RVS) machine is an innovative beneficiation machine designed for screening different mineral particles of varying sizes and volumes required by the customers' through the geometric transformation of its screen structure. The successful RVS machine upkeep requires its continuous, availability, reliability and maintainability. The RVS machine downtime, which could erupt from its breakdown and repair, must also be reduced to the barest minimum. This means, there is a need to design and develop a maintenance system model that could be used to effectively maintain the RVS machine when utilized in surface and underground mines. In view of this, this paper aims to develop a maintenance system model that could be used to effectively maintain the RVS machine when used in surface and underground mines. The maintenance system model unfolds the predictive (i.e. diagnosis and prognosis) algorithms, the e-maintenance strategic tools as well as the dynamic maintenance strategic algorithms required to effectively maintain the RVS machine. Four different case studies were presented in this paper to illustrate the applicability of this maintenance system model in maintaining and managing the RVS machine when utilized in the mining industries.
Keywords: 650; Reconfigurable vibrating screen; Reliability; Dynamic maintenance; Maintainability; LABVIEW®